2021
DOI: 10.1259/bjr.20210842
|View full text |Cite
|
Sign up to set email alerts
|

Serial changes in tumour measurements and apparent diffusion coefficients in prostate cancer patients on active surveillance with and without histopathological progression

Abstract: Objective: To analyse serial changes in MRI-derived tumour measurements and apparent diffusion coefficient (ADC) values in prostate cancer (PCa) patients on active surveillance (AS) with and without histopathological disease progression. Methods: This study included AS patients with biopsy-proven PCa with a minimum of two consecutive MR examinations and at least one repeat targeted biopsy. Tumour volumes, largest axial two-dimensional (2D) surface areas, and maximum diameters were measured on T2 weighted image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…As a result, the AUC of the most holistic model combining TSR and time series PSAd was the closest to that of an expert-derived PRECISE assessment, and it was also considerably higher than previously reported serial MRI performance pooled across different centres [ 7 ]. Finally, some radiomic features that passed the robustness analysis including Maximum 2D Diameter Row and Surface Area directly correspond to previously identified tumour measurements that are known to differ between progressors and non-progressors [ 32 , 33 ]. These findings suggest that TSR with or without the addition of time series PSAd may offer a quantitative and interpretable solution to standardising serial MRI assessment in AS, with potential to increase radiologists’ confidence and improve performance across centres and healthcare systems by achieving the expert-derived PRECISE standard.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, the AUC of the most holistic model combining TSR and time series PSAd was the closest to that of an expert-derived PRECISE assessment, and it was also considerably higher than previously reported serial MRI performance pooled across different centres [ 7 ]. Finally, some radiomic features that passed the robustness analysis including Maximum 2D Diameter Row and Surface Area directly correspond to previously identified tumour measurements that are known to differ between progressors and non-progressors [ 32 , 33 ]. These findings suggest that TSR with or without the addition of time series PSAd may offer a quantitative and interpretable solution to standardising serial MRI assessment in AS, with potential to increase radiologists’ confidence and improve performance across centres and healthcare systems by achieving the expert-derived PRECISE standard.…”
Section: Discussionmentioning
confidence: 96%
“…In patients undergoing AS, there were no significant differences in the growth rates of PCa tumors between grade I and grade II (18% vs. 23%, p=0.16), as determined by mpMRI [34]. However, another study identified tumor diameter and small-volume ADC as significant predictors of pathological progression during AS [35]. Specifically, a 20% increase in tumor diameter and a 10% decrease in small-volume ADC were proposed as threshold values.…”
Section: Serial Changes Of Mri During Asmentioning
confidence: 96%
“…Algohary, Ahmad, et al [14] evaluated the performance of radiomics in identifying the presence of clinically significant PCa in AS patients. A few other studies [15,16] focused on clinical features and/or a chosen set of shape and firstorder features extracted from MRI sequences for progression prediction. Albeit, these studies only included patients with MRI visible lesions wherein lesions served as the ROI for extracting radiomics features.…”
Section: Introductionmentioning
confidence: 99%